SCOUT3D – AN UNDERWATER LASER SCANNING SYSTEM FOR MOBILE MAPPING - M. Bleier; J. van der Lucht; A. Nüchter (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
This paper presents an underwater laser scanning system and GNSS based trajectory estimation system for scanning from a surface vessle in shallow water. The system has an above-the-water and an underwater component. Above-the-water two low-cost multiband GNSS receivers with an antenna baseline of one meter are used for RTK positioning with heading. The full 6-DOF is estimated by fusing the satellite navigation data with a MEMS-based INS. The 3D data is captured in water using a structured light scanner consisting of a low-light underwater camera and a green cross line laser projector. We describe the development of the system and employed hardware components. We show results of scanning a large test object in a water tank acquired by from a tripod with a motorized yaw axis. Additionally, we demonstrate first results of mobile mapping from a floating platform. We evaluate the performance of the system by measuring the 6-DOF trajectory with an external optical tracking system. Additionally, we assess the quality of the created point cloud using reference objects placed in the scene.